Excellent photocatalytic and photoelectrochemical activities from 1D/2D FeSe2/SnSe heterojunction photocatalysts constructed by FeSe2 nanorods and SnSe nanosheets. (5th February 2022) - Xiong, Xiaoshan; Zhang, Jun; Cheng, Yinsen; Chen, Chao; Zeng, Jinghui; Xi, Junhua; Kong, Zhe; Yuan, Yong-Jun; Ji, Zhenguo
Abstract: In this work, FeSe2 nanorods have been employed to be loaded on SnSe nanosheets to develop 1D/2D FeSe2 /SnSe heterojunction photocatalysts. These test results of XRD, SEM, HRTEM and XPS fully confirm the successful construction of FeSe2 /SnSe heterojunction. These results of photocatalytic and photoelectrochemical test further reveal that FeSe2 /SnSe heterojunction photocatalysts have excellent photocatalytic and photoelectrochemical activities. In comparison to the SnSe, the highest photocurrent density of the 1D/2D FeSe2 /SnSe heterojunction photocatalyst is 19.2 μA/cm 2, which has 123% promotion. Besides, the biggest degradation rates k of the 1D/2D FeSe2 /SnSe heterojunction photocatalyst is 0.00612 nearly 297% enhancement than the SnSe. Further analysis indicated that as for 1D/2D FeSe2 /SnSe heterojunction photocatalyst, its internal resistance was largely reduced and carrier separation efficiency was significantly improved with the recombination of FeSe2 . This work confirmed that FeSe2 /SnSe is an ideal composite system with great potential in photocatalysis. Graphical abstract: A new type of 1D/2D heterojunction was constructed by and FeSe2 SnSe which exhibits 2 times enhancement on photoelectrochemical activity and 4 times improvement in photocatalytic performance. Image 1 Highlights: 1D/2D FeSe2 /SnSe heterojunction photocatalysts were prepared. The photocatalytic and photoelectrochemical activity of the FeSe2 /SnSe is largely enhanced. The photocurrent of the FeSe2 /SnSe photocatalyst can reach 19.2 μA/cm 2 . The photocatalytic activity of the FeSe2 /SnSe photocatalyst has an enhancement of 3 times.